PENYIMPANGAN IDENTITAS DAN PERAN JENDER Pendekatan Penelitian Masalah Kesejahteraan Sosial Waria - Nina Karinina (Politeknik Kesejahteraan Sosial, 2007)
This paper discusses the problem of gender identity and role which concerns to sociopsychological deviations. The focus of discussion relates to socio-psychological deviation in the scope of transsexual social welfare. That deviation may develop many problems in the societal life, particularly for the transsexuals themselves. The problems which are experienced by transsexuals rooted on gender identity and roles, and this impact on their daily behaviour and avtivities. As the consequencies, the others who live arroud them look their behaviour as a deviation. Among other things which become problems to transexuals are related to job, the style of dressing, Haj pilgrim for Moslems, public toilet usage etc. There are many efforts done by transexuals to obtain their gender identities for legally acception from the government. Nevertheless, the proposal for their gender identities has not been accepted yet, as it is unline with the Indonesian legislation both formal and informal.The scientists, including researchers have roles on policies and programs formulation inputs in order to empowering transexuals to become a potential human resources. On the other hand, through experimental research the concept are tested through experimental research to obtain medical psychiatric and social psychological theories.Key Words : gender identities and roles, social psychological deviations, human resourcesempowerment.